Dynamic changes in hedonic and emotional responses to fruit varying in portion size. (December 2022) - Isabel Salazar Cobo, Maria; Jager, Gerry; de Graaf, Cees; Zandstra, Elizabeth H.
Highlights: Fruit is a highly liked food. Assessment of hedonic and emotional responses to low-energy dense foods (fruit) varying in portion size. Small and regular portions of fresh fruit are more enjoyed than a large portion. Small and regular portions of fresh fruit had similar emotional profiles (TDE) dominated by happy and relaxed. However, the last section of the large portion size, showed negative emotions as boredom. Abstract: The average intake of fruits across the world is lower than recommended. This lower intake of fruit is surprising as fruit is a typically liked food, and a higher liking is generally associated with a higher intake. The question then arises as to why do levels of fruit intake remain lower than recommended. This study investigated dynamic changes in hedonic and emotional responses to a fresh fruit salad consisting of pineapple, strawberries and blueberries. In a within-subjects design, 45 participants (aged 26.7 ± 4.6 years) randomly consumed three portion sizes of food (i.e. small, regular and large) across three sessions. The foods were divided into a first and last section of consumption. Before and after consumption, hunger and liking were measured. Throughout consumption, emotional responses were measured with Temporal Dominance of Emotions (TDE). Results showed that liking increased from before consumption till after consumption for all portions. The emotional profiles (TDE) of small, regular, and the first section of the large portion were dominated by happy and relaxed . However, the emotional profile for the last section of the large portion size, also showed negative emotions to become dominant, i.e. bored . These results show that large portions of fresh fruit salad may be less enjoyed by consumers as compared to eating a small or regular portion. This implies that consuming smaller portions of fruit on several occasions across the day, may serve the goal of meeting the recommended daily fruit intake better than eating a large portion of fruit in a single occasion. These findings contribute to a better understanding of how consumers perceive and respond to changes in portion size, and allow to address the effectiveness of portion size strategies for consumer health and wellbeing.